2013
DOI: 10.1007/s12032-013-0801-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 5/6, c-Met expressions, and PTEN loss prognostic indicators in triple-negative breast cancer

Abstract: In subgroups of breast cancer, the shortest disease-free and overall survival was observed in basaloid and human epidermal growth factor receptor-2 groups. CK5/6 expression is a marker used in diagnosing breast cancers in basaloid group and is associated with a poor prognosis. Similarly, loss of tumor suppressor gene PTEN and a high expression of c-Met has been associated with poor prognosis in breast cancer and many other cancers. In this study, we aimed to determine the effect of CK5/6 and c-Met expressions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 34 publications
5
43
1
1
Order By: Relevance
“…These immunohistochemical markers have been heavily used in breast cancer. CK5/6 is one of the basal-like subtype markers and its correlation with worst recurrence of patients with TNBC has been reported [28]. Loss of AR is associated with poor prognosis in patients with lymph node-positive ER/PR/ Her2-negative breast cancer [18].…”
Section: Discussionmentioning
confidence: 99%
“…These immunohistochemical markers have been heavily used in breast cancer. CK5/6 is one of the basal-like subtype markers and its correlation with worst recurrence of patients with TNBC has been reported [28]. Loss of AR is associated with poor prognosis in patients with lymph node-positive ER/PR/ Her2-negative breast cancer [18].…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, it has been demonstrated that c-met expression was an independent predictor of recurrence and death in triple negative BC. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Loss of phosphatase and tensin homolog (PTEN) expression has been reported in 37 to 74% of metastatic triple-negative breast cancers [14-16], which results in activation of the PI3K/PTEN/AKT/mTOR pathway, making mTOR inhibitors also a potential molecular target for treating TNBC [17,18]. Activation of the PI3K/AKT/mTOR pathway in breast cancer portends a worse prognosis, increased aggressiveness and resistance to treatment [19].…”
Section: Introductionmentioning
confidence: 99%